2021
DOI: 10.1107/s1600576721006592
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation contrast on X-ray topographs under weak diffraction conditions

Abstract: The contrast of dislocations in 4H-SiC crystals shows distinctive features on grazing-incidence X-ray topographs for diffraction at different positions on the operative rocking curve. Ray-tracing simulations have previously been successfully applied to describe the dislocation contrast at the peak of a rocking curve.The present work shows that the dislocation images observed under weak diffraction conditions can also be simulated using the ray-tracing method. These simulations indicate that the contrast of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The displacement fields of dislocations and their effect on XRT or other diffraction contrast images are well understood. Although it is still rather uncommon, MB-XRT (or “rocking curve imaging”) allows the quantification of these displacement fields and a direct comparison to theory . Another consequence is the apparent shift of the dislocation when inverting the sign of the angular detuning from the Bragg condition (used to achieve weak-beam contrast) as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The displacement fields of dislocations and their effect on XRT or other diffraction contrast images are well understood. Although it is still rather uncommon, MB-XRT (or “rocking curve imaging”) allows the quantification of these displacement fields and a direct comparison to theory . Another consequence is the apparent shift of the dislocation when inverting the sign of the angular detuning from the Bragg condition (used to achieve weak-beam contrast) as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…25 Monochromatic beam X-ray topography (MB-XRT), also referred to as double-crystal or plane-wave topography, allows enhancing the resolution for the imaging of dislocations by exploiting the so-called weak-beam contrast. 26,27 The typical energy bandwidth of ΔE/E ∼ 10 −4 of a double-crystal monochromator in combination with a highly parallel beam allows the strong suppression of diffraction signals from undistorted crystal regions, while selectively highlighting sufficiently distorted crystal regions only close to the dislocation cores. This leads to dislocation images with very narrow lines� usually with a width of only a few micrometers�and thus to an enhanced spatial resolution as compared, e.g., to WB-XRT.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the contrast of the defect is determined not only by the overlap or separation of diffracted X-rays but also by the intensity of individual X-rays following diffraction. Therefore, in order to apply ray-tracing simulations to interpret the dislocation images in synchrotron weak-beam topography (Peng, Ailihumaer, Liu et al, 2021) or plane-wave topography, the intensity of each of the diffracted X-ray beams must be taken into consideration.…”
Section: Ray-tracing Simulation With Enhanced Accuracymentioning
confidence: 99%
“…It is almost impossible to distinguish the sign of the Burgers vectors since there is no additional contrast outside the circle. Previous work by Peng, Ailihumaer, Liu et al (2021) showed that additional dislocation features could be revealed when the topographs were recorded on the flanks of the rocking curve where the maximum strain sensitivity is obtained (Klapper, 1996). In 0008 SXPWT, however, we show that even without going to the flanks the dislocations already exhibit distinct features on the topographs, since the RC width is more than one order of magnitude narrower and there is significant slope even near the peak.…”
Section: Dislocation Contrast In Xrtmentioning
confidence: 99%
See 1 more Smart Citation